Механизмы сезонной цикличности размножения птиц. Сообщение II. Анализ рефрактерного периода гонад у птиц - Новиков, Б.Г.; Руднева, Л.М. (Вестник зоологии, 1974)
The problem on the possible mechanisms of gonads transition to a refractory phase in birds after the reproduction is discussed on the basis of the literature data and results of the authors' own investigations. The season cyclicity of birds reproduction is shown to be connected with the year periodicity of synthesis and removal of gonadotropinreleasing hormones from the hypothalamus.
It is supposed that the mechanism of regulation of the refractory period is closed only at the level of hypothalamus, but this question requires the further study.